Applying the Microservices Architecture in the Development of an Online Fish Auction System - Irawan, Bei Harira; Prihadi, Deddy; Simarangkir, Manase Sahat; Miswadi, Miswadi; Sofyan, Ali (Journal of Artificial Intelligence and Software Engineering, 2025)
Online fish auction systems offer an innovative solution to improve efficiency and transparency in fisheries transactions. Using microservices architecture enhances scalability, flexibility, andperformance. Core services like user authentication, auction management, bidding, payment, and delivery are built independently with structured APIs. Performance testing with JMeter simulates active users to measure response time, throughput, and resource usage. Resultsshow the authentication endpoint averages 120ms response time, while auction management reaches 150ms. The system’s throughput increases by 45% over monolithic architecture, handling up to 5,000 requests per minute. Simulations reveal improved resource efficiency, with CPU usage reduced by 30% and memory by 25%. The study concludes that microservices offer an efficient and reliable digital fish auction solution. Another advantage of the microservices approach is the ease of maintenance and the development of new features without disrupting existing services. Each service can be horizontally scaled according to workload demands, allowing the system to remain responsive under high traffic conditions. Therefore, this system is suitable for national or regional implementation in supporting the digital fisheries ecosystem.